Insecticide Resistance Status and Mechanisms of Anopheles sinensis (Diptera: Culicidae) in Wenzhou, an Important Coastal Port City in China. Issue 3 (1st February 2019) - Chen, Shixin; Qin, Qian; Zhong, Daibin; Fang, Xia; He, Hanjiang; Wang, Linlin; Dong, Lingjun; Lin, Haiping; Zhang, Mengqi; Cui, Liwang; Yan, Guiyun
Abstract: Although scaled-up interventions and effective control efforts have drastically reduced malaria morbidity and mortality, malaria remains a serious threat to public health worldwide. Anopheles sinensis Wiedemann 1828 is a historically important vector of Plasmodium vivax (Haemosporida: Plasmodiidae) malaria in China. Insecticide resistance has become a major obstacle to vector-borne disease control. However, little is known about the insecticide resistance of An. sinensis in Wenzhou, an important coastal port city in Zhejiang province, China. The aim of this study was to examine insecticide resistance and mechanisms in An. sinensis field mosquito populations. Evidence of multiple insecticide resistance was found in An. sinensis adult female populations. Medium to high frequencies of target site kdr together with fixed ace-1 mutations was detected in both the Ruian and Yongjia populations. Both populations showed an association between kdr L1014 mutation and resistance phenotype when tested against deltamethrin and DDT. Significantly different metabolic enzyme activities were found between the susceptible laboratory strain and field-collected mosquitoes from both Ruian and Yongjia. Both field collected An. sinensis populations exhibited significantly higher P450 enzyme activity compared with the laboratory strain, while the field-collected resistant mosquitoes exhibited various GST and COE enzyme activities. These results indicate multiple resistance mechanisms in An. sinensis field populations. Effective implementation of insecticide resistance management strategies is urgently needed. The data collected in this study will be valuable for modeling insecticide resistance spread and vector-control interventions.